Melihat sejarah nasionalisme Indonesia untuk memupuk sikap kebangsaan generasi muda - Alfaqi, Mifdal Zusron (Jurnal Civics: Media Kajian Kewarganegaraan, 2016)
In the globalized era and the fragile nation, it is necessary for us to look backward (to learn) the history of Indonesian nationalism. It is due to the fact that in this era a lot of young generation tends to forget and choose to become competitive individuals and then ignore their nationality. Many young generations were trapped in temporary hedonism and rejected national spirit in the name of personal objectives. From the formation of Indonesian nationalism perspective, the role of young generation is inseparable such as Sumpah Pemuda (Youth Pledge). Accordingly, by considering the history of Indonesia nationalism, it is necessary for young generation to have an attitude as well as behave in the context of nationality.